Nominal Anchors in the CIS - Keller, Peter; Richardson, Thomas (Washington, D.C. : International Monetary Fund, 2003)
Monetary policy has become increasingly important in the countries of the Commonwealth of Independent States (CIS) as fiscal adjustment and structural reforms have taken root. Inflation has been brought down to relatively low levels in almost all of these countries, raising the question of what should be the appropriate nominal anchor at this stage. Formally, almost all CIS countries have floating exchange rate regimes, yet in practice they manage their exchange rates very heavily, perhaps because of high levels of dollarization (i.e., they suffer from "fear of floating"). This paper explores the issues underlying the choice of a nominal anchor in CIS countries and seeks to assess whether the present mixed regime will prove durable.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet